2008
DOI: 10.1016/j.jalz.2008.05.1081
|View full text |Cite
|
Sign up to set email alerts
|

P2‐001: High‐resolution magnetic resonance imaging to quantify relaxation parameters in Alzheimer's brain tissue

Abstract: 2016-12-24T18:07:49

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Inhibition of polymorphic Aβ aggregation is a promising approach to developing effective therapeutic agents for AD. , In this context, we studied the effect of our compounds 1 – 4 on metal-independent and -dependent Aβ42 aggregation, and compounds 1 – 4 showed minimal ThT fluorescence (24%, 17%, 26% and 18%, respectively) in comparison to that of Aβ42 alone, which is considered as 100%; GHK exhibited 78% ThT fluorescence (Figure S15). The data also revealed that the most promising antioxidant 4 inhibited Aβ42 aggregation by >80% compared to ∼20% by GHK.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Inhibition of polymorphic Aβ aggregation is a promising approach to developing effective therapeutic agents for AD. , In this context, we studied the effect of our compounds 1 – 4 on metal-independent and -dependent Aβ42 aggregation, and compounds 1 – 4 showed minimal ThT fluorescence (24%, 17%, 26% and 18%, respectively) in comparison to that of Aβ42 alone, which is considered as 100%; GHK exhibited 78% ThT fluorescence (Figure S15). The data also revealed that the most promising antioxidant 4 inhibited Aβ42 aggregation by >80% compared to ∼20% by GHK.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As there is significant heterogeneity in the microstructural distribution and bound states of iron [as observed in hippocampus ( Antharam et al, 2012 ) and SN ( Blazejewska et al, 2013 )], there is value in being able to directly describe the spatial relationship between iron and MRI. Given the limited sensitivity of routine iron histochemistry for this purpose [recently noted in postmortem analysis of iron and MRI in the SN ( Blazejewska et al, 2013 )], there have been growing efforts to correlate SXRF microscopy maps with the corresponding MRI data from post-mortem human tissue ( Collingwood et al, 2008a ; Hopp et al, 2010 ; Antharam et al, 2012 ). This has included studies in formalin-fixed tissue to achieve approximate correlations between susceptibility-weighted imaging (SWI) and iron maps for multiple anatomical regions in each case via the rapid SXRF approach ( Hopp et al, 2010 ), and for the first time in unfixed tissues, working at high spatial resolution in thin sections to match SXRF iron maps with R 2 and R 2 * maps, permitting detailed analysis of the hippocampus in AD cases and age-matched controls and demonstration of a positive correlation between iron and R 2 , R 2 * ( Antharam et al, 2012 ).…”
Section: X-ray Fluorescence Analysis Of Iron In Neurodegenerative Dismentioning
confidence: 99%